1995
DOI: 10.3354/meps127087
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and the uptake of cadmium and zinc by the amphipod crustacean Orchestia gammarellus

Abstract: ABSTRACT. The rates of uptake of cadmium and zinc by the amphipod crustacean Orchestia gammarellus (Pallas) increase with decrease in salinity from 36.5 to 25"% NaC1, as expected from physicochemical changes in the ava~labilities of free metal ions. Between 15 and 2.5':~~ NaCl cadmium and zlnc uptake rates plateau, and the cadmium uptake rate falls at 12% NaC1. This pattern of change of uptake rate with salinity change is not dependent on trace metal exposure concentrations, and cannot be explained by uptake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 14 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…Cd and Ca are uptake by an energy-requiring pump in the epithelial cell membrane and then accumulation in the carapace or other part that have high concentration of Ca 11,39 . This result was similar to the studies on amphipods (Orchestia gammarellus) by Rainbow et al 40 and Rainbow and Kwan 41 , which found that decreases in salinity produced predictable increases in metal uptake rate. This result was different from the study in Palaemon elegans and Palaemonetes varians by Nugegoda and Rainbow 42,43 that decreases in salinity could decrease concentration of metals.…”
Section: Discussionsupporting
confidence: 80%
“…Cd and Ca are uptake by an energy-requiring pump in the epithelial cell membrane and then accumulation in the carapace or other part that have high concentration of Ca 11,39 . This result was similar to the studies on amphipods (Orchestia gammarellus) by Rainbow et al 40 and Rainbow and Kwan 41 , which found that decreases in salinity produced predictable increases in metal uptake rate. This result was different from the study in Palaemon elegans and Palaemonetes varians by Nugegoda and Rainbow 42,43 that decreases in salinity could decrease concentration of metals.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, some aquatic invertebrates can affect the rate of trace metal uptake from solution by making a physiological response to changes in the medium, for example to salinity reduction (Rainbow et al 1993, Rainbow & Kwan 1995, Rainbow & Black 2002. Such physiological intercession that affects trace metal uptake rates is by no means a universal feature of aquatic invertebrates, and seems to be a characteristic of particular euryhaline estuarine invertebrates (Rainbow 1997, Rainbow & Black 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Reductions in salinity reduce the amount of chloride present and increase the percentage of dissolved cadmium present as the free metal ion (Rainbow et al 1993). Such physicochemical effects on the rates of uptake of trace metals by invertebrates are independent of the invertebrates themselves (Rainbow 1997, Rainbow & Black 2002.On the other hand, some aquatic invertebrates can affect the rate of trace metal uptake from solution by making a physiological response to changes in the medium, for example to salinity reduction (Rainbow et al 1993, Rainbow & Kwan 1995, Rainbow & Black 2002. Such physiological intercession that affects trace metal uptake rates is by no means a universal feature of aquatic invertebrates, and seems to be a characteristic of particular euryhaline estuarine invertebrates (Rainbow 1997, Rainbow & Black 2002).…”
mentioning
confidence: 99%
“…The relatively small decrease of Zn uptake at 8 psu also might be related to the change of free ionic activity. Assuming that the Cr(VI) speciation was influenced minimally by salinity, the constant Cr uptake among different salinities may indicate that the filtration rate and permeability of gill epithelium of C. fluminea might not be affected by salinity (Rainbow and Kwan 1995). Therefore, the influence of salinity on the Cd and Zn influx rate might be explained by the combined effects of speciation change and increased binding competitions related to major ions.…”
Section: Influx From the Dissolved Phasementioning
confidence: 99%
“…Many studies have evaluated the effect of salinity on the dissolved metal uptake (Fischer 1986;Nugegoda and Rainbow 1989a, b;Blust et al 1992;Chan et al 1992;Bjerregaard and Depledge 1994;Rainbow and Kwan 1995;Lee et al 1998). Euryhaline organisms living at low salinities generally contained higher concentrations of metals than those living at higher salinities (Phillips 1980).…”
Section: Influx From the Dissolved Phasementioning
confidence: 99%